2022
DOI: 10.3390/ijerph19127122
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nutrition Labelling on Customer Buying Intention and Behaviours in Fast Food Operations: Some Implications for Public Health

Abstract: This research examines customers’ intention to buy depending on their use of nutrition labelling (NL) in fast food operations (FFOs) and their intention to visit and recommend these FFOs with nutrition-labelled menus. The research model draws on the theory of planned behaviour (TPB) to examine customers’ intentions to buy from nutrition-labelled menus and their behaviour of visiting and recommending to others FFOs with nutrition-labelled menus. To achieve this purpose, a self-administrated questionnaire was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…These findings support previous research studies [22][23][24] where health consciousness significantly predicts consumers' intentions to purchase organic menus or local food items. In addition, the results support the TPB framework [15] and previous research [14] where the intention to buy NLMs significantly predicts intention to recommend NLM among consumers in both countries (the KSA and the UK). Moreover, the results confirmed a mediating role for intention to buy NLM in the relationship between the three antecedents (ATT, SNs, PBC), health consciousness and the intention to recommend NLMs among consumers in the KSA and the UK.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…These findings support previous research studies [22][23][24] where health consciousness significantly predicts consumers' intentions to purchase organic menus or local food items. In addition, the results support the TPB framework [15] and previous research [14] where the intention to buy NLMs significantly predicts intention to recommend NLM among consumers in both countries (the KSA and the UK). Moreover, the results confirmed a mediating role for intention to buy NLM in the relationship between the three antecedents (ATT, SNs, PBC), health consciousness and the intention to recommend NLMs among consumers in the KSA and the UK.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, consumers' purchase intentions predict their actual buying behaviour of state-branded products. A recent study adopted TPB to examine customers' intentions to buy nutrition-labelled items in fast food operations [14]. The results showed that only SNs and PBC significantly affect consumers' intentions to buy NLM.…”
Section: The Influence Of Tpb Determinants and Health Consciousness O...mentioning
confidence: 99%
See 2 more Smart Citations
“…Nutritional labels impact the consumer and the social environment, especially when consuming healthy products. For instance, when dining out, the people who matter to the consumer prefer to select a menu item that provides nutritional information ( 86 ). Similarly, Sousa et al ( 87 ) found that customers’ intentions to purchase products with nutritional labels were significantly related to their subjective norms, indicating that consumers are influenced by their peers when using food labels to select healthy foods.…”
Section: Theoretical Backgroundmentioning
confidence: 99%